The Importance of PPE Use in Construction Site - Md Ghazali, Filzah Nadzirah; Yusof, Yusmarwati; Ibrahim Mukhtar, Marina (Research and Innovation in Technical and Vocational Education and Training, 2022)
Employee safety issues in high-risk sectors such as the construction sector becomes a major concern as it involves hazardous work, prone to accidents, and the risk of injury. Safety is an important matter that needs to be emphasized by the employer in carrying out construction work. The Occupational Safety and Health Act (ACT 514) emphasizes on the importance and welfare needs of construction workers in the workplace. Therefore, this study is conducted to determine the use of Personal Protective Equipment (PPE) among construction workers while performing their work at the construction site. This study focuses on three aspects: knowledge, skills, and attitudes of construction workers on the importance of using PPE at construction sites. A questionnaire was employed as the main instrument to achieve the goals and objectives of the study. This study involved a total of 103 construction workers from three construction sites in the states of Johor and Selangor. All data obtained from the questionnaire were analyzed to obtain the frequency, percentage, mean score, and standard deviation. The results of the study found that the use of PPE among construction workers in the construction sector is high and at a satisfactory level. The mean score value for each construct in terms of knowledge, skills, and attitudes of construction workers towards the importance of PPE shows a high and good level. Overall, construction workers are concerned about using PPE while doing work on construction sites and are aware of the safety issues. This study is expected to provide useful input to all relevant parties in the construction sectors and in turn can improve safety management in the construction sectors for the sake of the workers and their careers, as well as for the employers.